Efforts of watershed sustainability and usage among peri-urban agricultural farmers of Kwadon, NE Nigeria - Ibrahim, Muhammad Bello; Ahmad, Nobaya; Abu Samah, Asnarulkhadi; Redzuan, Ma'arof (Einfomia Online, 2016)
This paper looks at efforts of farmers in sustainability and usage of Kwadon watershed in Gombe, NE Nigeria, involved in peri-urban agriculture (PUA). Sustainability concept was centred on seeing the earth as a system that connects environment, economy and society so that people can waste less, pollute less and create more things of value to the society. The study adopts a quantitative research approach. Primary data was drawn from an instrument administered to 217 respondents from a population of 500 PUA farmers. Krejcie and Morgan (1970) table was used to determine the sample size of the study, this choice was supported by G*Power Analysis Software 3.0 (Faul, Erdfelder, Lang & Buchner, 2007), all giving the same sample size at alpha (α)= 0.05 level of significance. Descriptive statistics was used to analyze the data for getting a meaningful discussion to the findings. Watershed sustainability issues such as sources of water to the farms, water sharing and watershed management were the main focus of quantitative data collected. The descriptive statistics results, using the IBM SPSS Version 20 for data analysis was used to understand the general trends and attitudes of farmers concerning their attitude towards sustainability of the Kwadon watershed, with statistics suggesting that majority of the PUA farmers are sustaining the watershed moderately through their farming practices. Lastly, the paper recommends increasing levels of sustainability through building of more social capital within the farming community by advocacy from local networks, government and non-governmental organizations.